Tilianin improves cognition in a vascular dementia rodent model by targeting miR-193b-3p/CaM- and miR-152-3p/CaMKIIα-mediated inflammatory and apoptotic pathways - Ting Sun; Linjie Tan; Mimin Liu; Li Zeng; Kaiyue Zhao; Zhongdi Cai; Shengnan Sun; Zhuorong Li; Rui Liu (Frontiers in Immunology, 2023)
IntroductionAlthough vascular dementia (VaD) is the second most prevalent form of dementia, there is currently a lack of effective treatments. Tilianin, isolated from the traditional drug Dracocephalum moldavica L., may protect against ischemic injury by inhibiting oxidative stress and inflammation via the CaMKII-related pathways but with weak affinity with the CaMKII molecule. microRNAs (miRNAs), functioning in post-transcriptional regulation of gene expression, may play a role in the pathological process of VaD via cognitive impairment, neuroinflammatory response, and neuronal dysfunction. This study aimed to investigate the role of tilianin in VaD therapy and the underlying mechanism through which tilianin regulates CaMKII signaling pathways based on miRNA-associated transcriptional action.MethodsRats with 2-vessel occlusion (2VO), a standard model of VaD, were treated with tilianin, vehicle control, and target overexpression or downregulation. High-throughput sequencing, qRT-PCR, and western blot analyses were utilized to identify the downstream target genes and signaling pathways of tilianin involved in VaD.ResultsOur results showed that tilianin ameliorated cognitive deficits, neurodegeneration, and microglial and astrocytic activation in rats with 2VO. Subsequent high-throughput sequencing and qRT-PCR analyses revealed that tilianin increased the downregulated miR-193b-3p and miR-152-3p levels in the cortex and hippocampus of 2VO rats. Mechanistically, miR-193b-3p targeting CaM and miR-152-3p targeting CaMKIIα were identified to play a role in VaD-associated pathology, inhibiting the p38 MAPK/NF--κB p65 pathway and decreasing TNF-α and IL-6 levels. Further gain- and loss-of-function experiments for these key genes showed that tilianin-exerted cognitive improvement by activating the p38 MAPK/NF--κB p65 and Bcl-2/Bax/caspase-3/PARP pathways in the brain of 2VO rats was abolished by miR-193b-3p and miR-152-3p inhibition. Moreover, CaM and CaMKIIα overexpression eliminated the elevated effects of miR-193b-3p and miR-152-3p on tilianin’s protection against ischemic injury through increased inflammatory reactions and apoptotic signaling.DiscussionTogether, these findings indicate that tilianin improves cognition by regulating the miR-193b-3p/CaM- and miR-152-3p/CaMKIIα-mediated inflammatory and apoptotic pathways, suggesting a potential small-molecule regulator of miRNA associated with inflammatory signaling for VaD treatment.